Structural Analysis and In-Silico Inhibitor Interaction Studies of Leishmania donovani Heat-Shocked Proteins 83 (HSP83) - Mansuri, Rani; Diwan, Anupama; Kumar Mundotiya, Pankaj; Singh, Jagbir (International Journal of Life Science and Pharma Research, 2022)
Leishmaniasis is a parasite disease prevalent in 88 nations worldwide, causing high morbidity and mortality in most developing countries. Since no vaccine or pharmaceutical treatment with the best therapeutic window is available, the World Health Organization has listed Leishmaniasis as a priority disease. The enzyme heat shock protein 83 (Hsp83), which is frequently found in cells, catalyzes cellular biological pathways to carry out tasks such as protein folding, intracellular protein trafficking, acquired thermotolerance, differentiation, adaptability, pathogenicity, persistence in the host cell and preventing proteins from being damaged by heat and other stresses. Therefore, HSP actively rewires cellular functions and signalling pathways, which is crucial for cell survival. Inhibition of HSP may interfere with pathogenesis and virulence by impairing several processes. Therefore, L. donovani heat shock protein 83 (LdHsp83) has been suggested as a potential leishmaniasis therapeutic target. Thus, in this study, we built the structure of HSP83 by homology modelling. We used Leishmania primary HSP90 crystal structure (PDB ID 3HJCA) as a template for constructing 3D models of LdHSP83 by comparative modelling approach using SWISS-MODEL, Phyre, GENO 3D program server and Prime 2.1 (Maestro 9.1, Schrodinger 2010) program tool. Based on overall stereochemical quality (PROCHECK, DOPE, Verify 3D), the best model was selected and further used for structural analysis. The energy-minimized, refined and characterized model was further investigated for antileishmanial activity with currently available antileishmanial drugs and enumerated virtual library of chemical compounds through a docking approach. A few combinations, including oxmetidine, had an excellent binding affinity with the Hsp83, as indicated by Glide Score (G Score) and Gold Fitness Score. These potential inhibitors were further studied for SAR and ADMET properties, respectively, by TSAR 3.3 and Qikprop 2.3, indicating the safety and efficacy of these compounds. Once preclinically and clinically examined, these compounds may further be implemented in leishmaniasis therapy.